Analysis of quality of grain shortbreads for biological activity and medicalbiological assessment - Mardar, Maryna; Vikul, Svitlana; Znachek, Rafaela; Bordun, Tetiana (Eastern-European Journal of Enterprise Technologies, 2018)
Quality control of new speltbased grain crispbreads with the addition of plant additives by the biological activity and medicobiological assessment was examined and analyzed. It was found that plant additives (powders from milk thistle, mountain ash and dog rose fruit) possess a high biological activity. The powders of dog rose and mountain ash are characterized by the high value the activity, which is 2,375 conditional units and 1,250 conditional units, respectively. The value of biological activity of spelt is by 2.55 times higher than that of wheat and is 156 conditional units. The introduction of additives to the composition of crispbreads increases the biological activity of finished products. The grain loaves with the addition of dog rose and ash has the highest biological activity, which is 300 conditional units. and 265 conditional units, respectively. In terms of biological activity, the synergy effect of BAS of original components was detected, while the effect of antagonism was not recorded. A comparative analysis of biological activity of grain crispbreads and crispbreads of wellknown brands revealed that the new products are characterized by a high value of biological activity. This attests to the prospects of development and bringing out to consumer market of the new speltbased products. The results of medicalbiological research prove the results of biological activity and indicate that the developed grain crispbreads possess antioxidant activity and hepatoprotective action. This is proved by the indicators of the level of hepatic markers that indicate the hepatoprotective effectiveness of the products. The results of the impact of the additive on dysbiosis degree and on the MDA content revealed that the new products with the addition of milk thistle have antioxidant properties. Based on the research, the expediency of manufacturing new grain speltbased crispbreads with the addition of enriching additives was substantiated. This enables us to obtain wellness products with a high biological activity and prophylactic properties